Letter to Mayor Jane Tolmach from Antonio Salcedo Sahagun - Antonio Salcedo Sahagun:::::: (1973)
A letter from Antonio Salcedo Sahagun, Municipal President of the city of Ocotlán, Jalisco, Mexico to Mayor Jane Tolmach sending well-wishes and a strong between the two cities.